2020
DOI: 10.1049/iet-ipr.2019.1458
|View full text |Cite
|
Sign up to set email alerts
|

Two viewpoints based real‐time recognition for hand gestures

Abstract: It is extremely challenging to accomplish excellent accuracy for gesture recognition using an approach where complexity in computation time for recognition is less. This study compares accuracy in hand gesture recognition of a single viewpoint set‐up with proposed two viewpoint set‐up for different classification techniques. The efficacy of the presented approach is verified practically with various image processing, feature extraction and classification techniques. Two camera system make geometry learning and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Gesture recognition detection was performed on the machine heat applying the system, and the results showed that its accuracy reached more than 90%, which can meet educational needs [17]. Kumar, A. K and other scholars conceptualized a system with low computational time complexity to achieve good gesture recognition accuracy, and comparative experiments pointed out that the recognition rate was better than but camera system, and the simple classifiers used, such as nearest neighbor and decision tree, also have good performance [18]. Scholars such as D. García-Santos discussed the differences between referee gender on technical interventions and stressful situations in basketball, using the IOVAB instrument to calculate the differences between technical interventions and LISEA questionnaires for observation and found that the implementation of an intervention program is necessary to regulate referee anxiety before and after the game [19].…”
Section: Introductionmentioning
confidence: 99%
“…Gesture recognition detection was performed on the machine heat applying the system, and the results showed that its accuracy reached more than 90%, which can meet educational needs [17]. Kumar, A. K and other scholars conceptualized a system with low computational time complexity to achieve good gesture recognition accuracy, and comparative experiments pointed out that the recognition rate was better than but camera system, and the simple classifiers used, such as nearest neighbor and decision tree, also have good performance [18]. Scholars such as D. García-Santos discussed the differences between referee gender on technical interventions and stressful situations in basketball, using the IOVAB instrument to calculate the differences between technical interventions and LISEA questionnaires for observation and found that the implementation of an intervention program is necessary to regulate referee anxiety before and after the game [19].…”
Section: Introductionmentioning
confidence: 99%
“…With the widespread application and development of digital libraries, the role of facial recognition is becoming increasingly important [ 1 ]. The application of facial length and angle feature recognition technology can improve the intelligent and personalized service quality of libraries [ 2 ]. On a global scale, the construction of digital libraries is no longer just a repository of knowledge, but also a creator and distributor of knowledge, becoming the center of communities and an important place for learning [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sharma et al [ 7 ] used a convolutional neural network to recognize images of Indian sign language gestures collected with an RGB camera. Kumar et al [ 11 ] proposed two viewpoint-set-up gesture classification methods. Their experimental results show that compared with a single-camera system, this method has high classification accuracy even when simple classifiers such as nearest neighbors and decision trees are used.…”
Section: Introductionmentioning
confidence: 99%